Spirits and the Proclamation of Christ 1 Peter 3:18-22 in Light of Sin and Punishment Traditions in Early Jewish and Christian Literature - Pierce, Chad T. (Mohr Siebeck, 2011)
Geister und die Predigt Christi. 1 Petrus 3, 18-22 vor dem Hintergrund der Schuld-und-Sühne-Traditionen in der frühjüdischen und christlichen Literatur.
PublicationDate: 20191210
Keywords: Composition/Redactio -- Evil Spirits -- 1 Peter Watchers -- Giants -- Neues Testament -- Antike -- Array